1‐Arylvinyl formats: A New CO Source and Ketone Source in Carbonylative Synthesis of Chalcone Derivatives. Issue 21 (19th February 2019) - Qi, Xinxin; Lai, Ming; Zhu, Min‐Jie; Peng, Jin‐Bao; Ying, Jun; Wu, Xiao‐Feng
Abstract: 1‐Arylvinyl formates as a kind of new CO surrogate have been explored for the first time. Most of the known CO precursors usually produce undesired residuals, which have to be removed. In this strategy, after CO release, the in situ generated acetophenones from 1‐arylvinyl formates can be successfully applied as a good ketone source in the synthesis of chalcones with benzaldehydes via a palladium‐catalyzed reductive carbonylation reaction. A variety of chalcones were isolated in satisfactory to good yields with good substrates compatibilities under mild conditions. Abstract : Surrogates needed : 1‐Arylvinyl formates as efficient and convenient CO surrogates have been explored for the first time. In this strategy, after CO release, the in situ generated acetophenones from 1‐arylvinyl formates could be successfully applied as a good ketone source in the synthesis of chalcones with benzaldehydes via a palladium‐catalyzed reductive carbonylation reaction. A variety of chalcones were isolated in moderate to excellent yields with good substrates compatibilities under mild conditions.